2010
DOI: 10.1590/s1807-59322010000700004
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and Electrolyte Balance During the First Week of Life and Risk of Bronchopulmonary Dysplasia in the Preterm Neonate

Abstract: BACKGROUND:Early fluid and electrolyte imbalances may be associated with an increased risk of bronchopulmonary dysplasia.OBJECTIVE:We sought to establish an association between fluid and electrolyte balance in the first week of life and the risk of bronchopulmonary dysplasia.METHODS:Clinical charts of 205 neonates <32 weeks gestational age and/or <1,250 g birth weight (admitted to our NICU between 1997 and 2008) were analyzed. Clinical features, fluid and electrolyte balance were analyzed for the first 7 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
(36 reference statements)
0
25
1
Order By: Relevance
“…Others have noted a similar effect of fluid provision and clinical outcomes, but have used different surrogate markers of fluid homeostasis [22, 23]. Because fluid provision is a potentially modifiable risk factor and there is wide clinical practice variance on the amount of fluid prescribed to premature infants, this observation needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have noted a similar effect of fluid provision and clinical outcomes, but have used different surrogate markers of fluid homeostasis [22, 23]. Because fluid provision is a potentially modifiable risk factor and there is wide clinical practice variance on the amount of fluid prescribed to premature infants, this observation needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Oh et al reported the association between fluid intake and weight loss during the first 10 days of life and the risk of BPD in extremely low birth weight infants [22]. In 2010, Rocha et al showed an association between fluid and electrolyte balance in the first week of life and the risk of BPD in preterm neonates [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Rocha et al (22) found that differences in renal function and tubular handling of potassium and phosphorus are present during the first week of life among preterm neonates who will develop bronchopulmonary dysplasia. The authors also found that patent ductus arteriosus and increased indomethacin use accentuate those differences.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Assessing kidney function is crucial for meticulous fluid, electrolyte, and nutritional support, and the adjustment of medication dosage in extremely preterm infants (EPT) [1][2][3][4]. Serum creatinine level (sCr) is a commonly used in evaluating renal function and could also be applied in assessment of glomerular filtration rate (GFR) in neonates and infants [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…AKI in premature infants are known to be related to increased mortality [11,[17][18][19][20][21] and morbidities, which includes bronchopulmonary dysplasia (BPD) [2,22,23] and intraventricular hemorrhage (IVH) [24]. However, these associations have not been well reported and elucidated in EPT, although J. Clin.…”
Section: Introductionmentioning
confidence: 99%